2013
DOI: 10.1002/jgrd.50687
|View full text |Cite
|
Sign up to set email alerts
|

Timescale dependence of aeolian sand flux observations under atmospheric turbulence

Abstract: [1] The transport of sand in saltation is driven by the persistently unsteady stresses exerted by turbulent winds. Based on coupled high-frequency observations of wind velocity and sand flux on a desert dune during intermittent saltation, we show here how observations of saltation by natural winds depend significantly on the timescale and method used for determining shear stress and sand flux. The correlation between sand flux and excess shear stress (stress above a threshold value) systematically improves for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 114 publications
7
52
0
Order By: Relevance
“…The reduced correlation between F wd and u * at small time resolution corroborates the correlation reduction observed between the saltation flux and u * by Sterk et al (1998), Shao and Mikami (2005), or Martin et al (2013), although the methods used by these previous studies were less suited than the wavelet method to estimate u * at small time scale, as explained in section 2.1. Shao (2008) suggested that this reduced correlation between saltation flux and near-surface u * at small time scale could be either explained (1) by the difference at small scales between near-surface and surface values of u * or (2) by the absence of saltation equilibrium state at small time scales where the second Owen's (1964) hypothesis of the skin friction equal to the fluid threshold shear stress would not remain.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The reduced correlation between F wd and u * at small time resolution corroborates the correlation reduction observed between the saltation flux and u * by Sterk et al (1998), Shao and Mikami (2005), or Martin et al (2013), although the methods used by these previous studies were less suited than the wavelet method to estimate u * at small time scale, as explained in section 2.1. Shao (2008) suggested that this reduced correlation between saltation flux and near-surface u * at small time scale could be either explained (1) by the difference at small scales between near-surface and surface values of u * or (2) by the absence of saltation equilibrium state at small time scales where the second Owen's (1964) hypothesis of the skin friction equal to the fluid threshold shear stress would not remain.…”
Section: Discussionsupporting
confidence: 69%
“…This is explained by variations of mesoscale background conditions, adding to the diurnal cycle forcing. This explains that an increasing number of studies focused on the smaller time scale behavior (<10 min) of the saltation flux in regard to the instantaneous shear stress and wind velocity, added to the fact that high-frequency sensors became more affordable these days (Bauer et al, 1998;Butterfield, 1991;Martin et al, 2013;Namikas et al, 2003). Even so, current parametrizations of the saltation flux still differ substantially from one to the other (Sherman and Bailiang, 2012), with 10.1029/2019JD031192 systematic differences between wind-tunnel and field measurements (Raupach, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments further revealed that, above the region of strongly suppressed near‐surface wind, there is a focal region at which the wind velocities are nearly constant with u * (the Bagnold focus ): uf≃Îș−1u*lnfalse(zffalse/zofalse) (Bagnold, ), where z f and u f are constants. This focal point approximation is equivalent to an exponentially increasing surface roughness, zo=zfexpfalse(−Îșuffalse/u*false), as found in simulations (DurĂĄn et al, , ) and measurements (Creyssels et al, ; Ho et al, ; Martin et al, ) of saturated saltation transport. In contrast, z o changes much more slowly with u * when saltation transport is strongly undersaturated or absent: z o ≃const.…”
Section: Wind Tunnel Experimentsmentioning
confidence: 85%
“…In contrast to the static threshold above which saltation can be initiated (e.g., Bagnold, ; Burr et al, ; Chepil, ; de Vet et al, ; Gillette et al, ; Iversen & Rasmussen, ; Iversen et al, ; Merrison et al, ; Nickling, ; Raffaele et al, , and references therein), u t has only rarely been systematically studied in controlled laboratory settings, especially in recent history (there are numerous poorly controlled field studies though; Barchyn & Hugenholtz, ; Li et al, ; Martin & Kok, , ; Martin et al, , and references therein). Even today, we largely rely on the old data sets by Bagnold () and Chepil (), who measured u t by visual means.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, sand transport could still be observed within long-time runs even though the fitted values of bed shear stress using conventional laboratory equations for mass transport predicted that there should be no transport (Rasmussen and SĂžrensen, 1999). By analyzing the observed data, many believe that the quasi-coherent structure in the turbulent wind in atmospheric surface layer is crucial to the intermittent saltation (e.g., Bauer et al, 1998;Baas, 2007;Martin et al, 2013), and the variability should be incorporated into the classical steady transport models. In the wind tunnel, Butterfield (1998) reported an obvious increase of induced transport which was much higher than the measured value in steady wind when imposing sinusoidal wind velocity variations with periods of 6-20 s. The results demonstrated the significant effects of unsteady wind on sand transport rate.…”
Section: Introductionmentioning
confidence: 95%